Work, education and structural crisis of capital - Rossi, Rafael (Geosaberes; Vol 8 No 14 (2017): Jan - Apr, 2017)
This article is an instrument by which we question the links between the social complex of education and work both in ontological sense, as with regard to the contradictions that are accentuated in the current period of structural crisis of capital. In this sense, a reflection that understands the limits of educational practice and the potential it presents for a critical and profound understanding of reality in a revolutionary posture and orientation is required.